Efficacy of Topical Administration of Corticosteroids for the Management of Dry Eye Disease: Systematic Review and Meta-Analysis - Julia Prinz; Nicola Maffulli; Matthias Fuest; Peter Walter; Andreas Bell; Filippo Migliorini (Life, 2022)
The efficacy of corticosteroids (CS) for dry eye disease (DED) has been investigated in the clinical setting. The present study investigated whether topical CS application improves the clinical outcome at last follow-up compared to the baseline. The present study was conducted according to the PRISMA 2020. All the randomized clinical trials (RCTs), which investigated the efficacy of corticosteroids in the management of DED, were accessed. In September 2022, the following databases were accessed: Pubmed, Web of Science, Google Scholar, and Embase. The following data were extracted at baseline and at last follow-up: Ocular Surface Disease Index (OSDI), tear breakup time test (TBUT), Schirmer I test (SIT), and corneal staining. Data from 425 patients were retrieved. A total of 69.4% (295 of 425 patients) were women. CS were effective to improve SIT (p = 0.02) and corneal staining (p = 0.003) at the last follow-up of 10.0 ± 15.3 weeks. TBUT was greater in the CS than in the control group at the last follow-up (p = 0.002). Concluding, topical CS administration led to an increase of SIT and a reduction of corneal staining at a mean of 10 weeks follow-up in patients with DED. Compared to a control group, topical CS administration evidenced greater values of TBUT. Altogether, a good safety profile was witnessed in DED patients receiving CS. However, different safety profiles of different CS formulations were not investigated due to a lack of quantitative data. The exact dosing frequency, duration of therapy, and favorable potency of the CS are still under investigation. Future randomized, controlled trials with larger sample sizes are warranted to provide higher-quality evidence to establish the role of CS in DED.